Upgrading Characteristics of Empty Fruit Bunch Biopellet with Addition of Bintaro Fruit as Co-firing - Idral Amri; Aris Aprianto Cahyono; Bahruddin (Journal of Bioprocess, Chemical and Environmental Engineering Science, 2021)
The low density of mass and energy are the main reason for the underutilization of great potential of Empty Fruit Bunch (EFB) as a raw material of alternative and renewable fuels. The using of bintaro fruit as co-firing and treatment of torrefaction – densification processes were believed to increase the density of mass and energy of the EFB biopellet. This study aims to determine the effect of residence time, compaction pressure, and addition of bintaro fruit to the characteristics of EFB biopellet according to ISO 17225-6 standards. Biopellet manufacture was carried out two processes sequence, namely the torrefaction process and the densification process. The torrefaction process was carried out at 275oC with residence time variations 30, 45, and 60 minutes. The densification process was carried out without binder with compaction pressure variations 30, 40, and 50 bar. The addition of bintaro fruit was intended as co-firing of EFB at a ratio 70:30. The best characteristics of biopellet were obtained under conditions of 60 minutes residence time and 50 bar compaction pressures with 3.00% of moisture content, 7.90% of ash content, 8.70% of volatile content, 80.40% of fixed carbon content, 4719.59 cal/gr of heating value, and 1.28 gr/cm3 of density. Characteristics of moisture content and volatile content decreased while ash content, fixed carbon content, and heating value increased with increasing residence time. Characteristics of density increased with increasing compaction pressure. Characteristics of proximate and heating value increased while density properties of biopellet decreased with the addition of bintaro fruit as co-firing.